Working with coaches and their teams in youth and collegiate sport in the USA: An interview with Dr Andy Gillham - Commentary - Trudel, P. (International Journal of Sports Science & Coaching, 2018)
In a constantly changing environment where there is danger of drowning in an overabundance of information, the optimal goal in helping others is not so much to give solutions but to provide the necessary conditions to favour meaningful learning. From what was presented in the article, Dr. Gillham has applied one of the `golden threads` listed by Hawkins and Smith regarding their coaching practice: Adult human beings learn best through experience, not by being taught or told. The work of the learning enabler is never to know better and never know first, but to create the enabling conditions and the experiences that create a transformational shift in the relationship and the individual.